Clinical feasibility of auditory processing tests in Japanese older adults: a pilot study. - Fujimoto, Shohei; Maeda, Yukihide; Obuchi, Chie; Uchida, Yasue; Harashima, Tsuneo; Nishizaki, Kazunori (Acta Oto-Laryngologica, 2019)
Background: Difficulty in listening comprehension is a major audiological complaint of older adults. Behavioural auditory processing tests (APTs) may evaluate it. Aims/Objectives: The aim was to assess the feasibility of administering Japanese APTs to older adults at otolaryngology clinics. Material and Methods: Using computer programs interfaced with an audiometer, APTs (dichotic listening test; fast speech test, FST; gap detection test, GDT; speech in noise test; rapidly alternating speech perception test) were administered to 20 older adults (65–84 years old; mean 75.3 years) and 20 young adults at the 40 dB sensation level. Monosyllable speech perception (MSP) and the Mini-Mental State Examination (MMSE) were evaluated. Results: APT results except for GDT were significantly correlated with MSP. The performance on each APT was worse in older adults than in young adults (p <.01). The older adults with good MSP ≥ 80% (n = 13) or excellent cognitive function (MMSE ≥ 28; n = 11) also did worse on APTs (p <.05). A ceiling effect was noted in the APT data, with FST showing a minimum ceiling effect and reflecting interindividual variations of data. Conclusions and Significance: It is feasible to administer APTs to older adults who visit otolaryngology clinics. Among our Japanese APTs, FST may be suitable for further large-scale clinical studies.